2013
DOI: 10.1111/eth.12094
|View full text |Cite
|
Sign up to set email alerts
|

Distance from Water, Sex and Approach Direction Influence Flight Distances Among Habituated Black Swans

Abstract: In many animals, response to predators occurs at greater distances the further an individual is from a refuge, but this has rarely been investigated in birds. Here, we test the hypothesis that the further from refuge (i.e. water) a foraging black swan Cygnus atratus is situated, the longer its flight initiation distance (FID) in response to a pedestrian approach on land. As predicted, swans situated farther from water exhibited longer FIDs compared with those closer to the shore. In addition, there was the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 37 publications
0
36
1
Order By: Relevance
“…Guay et al 2013a). All researchers have used consistent methods for data collection (following for example Weston et al 2012;Guay et al 2013c;van Dongen et al 2015a). Essentially, an investigator approaches a bird and measures the distance at which: (1) the approach began (Starting Distance; SD), (2) the bird became vigilant (AD; if possible) and (3) the distance at which it initiates escape (FID).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guay et al 2013a). All researchers have used consistent methods for data collection (following for example Weston et al 2012;Guay et al 2013c;van Dongen et al 2015a). Essentially, an investigator approaches a bird and measures the distance at which: (1) the approach began (Starting Distance; SD), (2) the bird became vigilant (AD; if possible) and (3) the distance at which it initiates escape (FID).…”
Section: Data Collectionmentioning
confidence: 99%
“…FID data in response to a wide variety of human-associated stimuli have already been collected on Australian bird species by our research team, including single pedestrians (e.g. Blumstein 2003;Guay et al 2013c;Møller et al 2014), groups of pedestrians (e.g. McLeod et al 2013), leashed dogs (e.g.…”
Section: Data Collectionmentioning
confidence: 99%
“…The site contains a 48.5-ha artificial lake with extensive grassy areas around its perimeter, where the Swans often forage (Guay et al 2013a). Most individuals at the study site had been fitted with neck collars displaying a unique identification number, allowing accurate individual identification at a distance (Guay & Mulder 2009, Mulder et al 2010.…”
mentioning
confidence: 99%
“…Flight-initiation distance depends on both starting distance (Blumstein 2003) and the distance from the closest refuge (Guay et al 2013a), we included starting distance and distance from the shoreline as covariates in our models. Standardization of starting distances was deemed unfeasible, so we statistically controlled them as is commonly done (McGiffin et al 2013, RodriguezPrieto et al 2009).…”
mentioning
confidence: 99%
“…A meta-analysis of risk assessment performed by Stankowich and Blumstein (2005) concluded that predator traits and increased distance of a prey animal from a refuge both consistently increase the potential prey's perception of risk, and therefore flight initiation distance. Other researchers have assessed factors such as light level (Cloyed and Eason 2015), the presence of a mating opportunity (Cooper 2011), level of concealment (Camp et al 2012), body size (Cloyed and Eason 2015), and the gender of the animal approached (Guay 2013).…”
Section: Introductionmentioning
confidence: 99%